The Role of the Codex Alimentarius in Determining International Standards for Pesticides and Food - Frederick M. Fishel (EDIS)
People have the right to expect their food to be safe, of good quality, and suitable for consumption, and national governments must ensure that food imported from other countries is safe. But laws and regulations to minimize threats can create barriers to international food trade. The Codex Alimentarius aims to facilitate international trade by promoting definitions and requirements for foods. This 3-page fact sheet was written by F.M. Fishel, and published by the UF Department of Agronomy, August 2011. (image from usda.gov)